Perancangan ulang konfigurasi baterai pada sepeda motor konversi listrik - Hendrawan, Muhammad Syarif Jayeng; Nugraha, Bintang; Herlambang, Yanuar (Institut Seni Indonesia Yogyakarta, 2025)
Electric motorcycle conversion programs in Indonesia face multiple challenges, including suboptimal battery configuration systems that compromise safety, comfort, and spatial efficiency. This study aims to redesign the battery configuration system of the Yamaha Mio Xeon GT 125 converted electric motorcycle using a user-centered Design Thinking approach. Key issues identified include poor battery ergonomics, safety risks due to inadequate ventilation, and disruption of the motorcycle’s aesthetic integrity. The design process follows five stages: empathizing with users, problem definition, ideation, digital 3D prototyping, and simulation-based testing using CAD software. The outcome is a new battery housing concept relocated to the center deck, utilizing steel plate, rubber, and ABS materials for protection. Evaluation results demonstrate improved vehicle stability and more accessible charging without sacrificing visual coherence. In conclusion, the optimized design effectively addresses technical and ergonomic shortcomings and has the potential to enhance user safety and comfort in daily electric motorcycle use.